Lung Decortication With Argon Plasma Energy for the Treatment of Chronic Pleural Empyema. Issue 4 (July 2021) - Lampridis, Savvas; Mitsos, Sofoklis; Lawrence, David R.; Panagiotopoulos, Nikolaos
Lung decortication for the treatment of chronic pleural empyema remains a technically challenging procedure that is associated with bleeding and air leak. The recent advent of pure argon plasma has provided thoracic surgeons with an electrically neutral energy source for dissection and coagulation of pulmonary tissue with minimal depth of necrosis. In this article, we describe the technique of lung decortication with argon plasma energy (PlasmaJet, Plasma Surgical, Roswell, GA, USA) for the treatment of chronic pleural empyema. With appropriate application, the PlasmaJet can facilitate the removal of fibrous cortex with satisfactory hemostasis and aerostasis. Argon plasma energy can potentially be a useful adjunct in lung decortication. Controlled trials are needed to determine its role in the surgical management of advanced pleural empyema.